Headaches in juvenile systemic lupus erythematosus patients: a cross-sectional study - Cajado, Bryan Silva Marques; Andrade, Renata Lopes Francisco; Pereira, Maria Angelina Carvalho; Aragão, Marcelo Melo; Terreri, Maria Teresa (Arquivos de Neuro-Psiquiatria, 2025)
Juvenile systemic lupus erythematosus (jSLE) often involves the central nervous system, with headache being the most common symptom.To describe the frequency, characteristics, and impact on quality of life of headaches in jSLE patients.We conducted a cross-sectional study with jSLE patients under the age of 19 years through chart reviews and questionnaires. The participants underwent clinical and neurological exams, assessments of disease activity and damage, and evaluations of headache characteristics. Quality-of-life impacts were measured using the Brazilian Portuguese version of the Pediatric Quality of Life Inventory (PedsQL), and cognitive function was assessed with the Mini-Mental State Examination.Out of 34 patients enrolled, 17 presented with headaches (which were more prevalent in female subjects). The age of the patients at the time of the evaluation ranged from 8 to 18 years, and the mean age at headache onset was of 11.3 years. Most participants with headaches reported having episodic headaches (76.5%), no perimenstrual crises (73.3%), and a family history of migraines (88.2%). Additionally, most patients reported physical activity (35.3%) and stress (58.8%) as triggers. Patients with headaches had significantly lower PedsQL scores compared with those without headaches, both in health and activities (61.76 versus 73.71 respectively; p = 0.04) and feelings (42.65 versus 60.35 respectively; p = 0.049).Headaches were more prevalent in female jSLE patients, and the most subjects experienced migraines as the primary cause of headache. Patients with headaches presented lower scores on quality-of-life questionnaires. These findings highlight the need for a comprehensive approach to headache management in jSLE to enhance patient well-being.
Keywords: Headache; Lupus Erythematosus, Systemic; Migraine Disorders; Quality of Life; Pediatrics